Língua(gem) e processos identificatórios no ensino-aprendizagem de línguas - Queiroz, Maria Cledir Zilli (2009)
This dissertation investigates the identification processes that affect the constitution of the subject-identity students considering a language crossed by the conception of heterogeneity, which is betweenlanguage or as the subject matter falls within discourses of the language. For this reason, question the unicity of language, pointing to the presence of the other /Other in saying, including the effects of meaning produced in the formation of subjects and their discourses, immersed in the wrong and unconscious processes. Evidenced epistemological issues concerning the field of discourse analysis (AD) as well as issues related to processes of identification of subjects, from identities in the process of construction and of psychoanalytic theory (rereading of Freud and Lacan). The body of research consists of texts produced in the mother tongue and foreign language, represented in this study, respectively, by the Portuguese and English, for students the first year of high school to a state school in São Borja. For the analysis of two cuttings of selected texts produced in the lassroom, the study concludes that the teaching-learning of languages is very complex and involves, besides the acquisition of knowledge and skills, the reconfiguration of subjective and identity processes that constitute the subject-student, through socio-historical processes and unconscious in symbolic and imaginary relations produced in and by history